1997
DOI: 10.1038/sj.bjp.0701146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nociceptin hyperalgesia and allodynia in conscious mice

Abstract: 1 Intrathecal (i.t.) administration of nociceptin and high doses of morphine induced allodynia in response to innocuous tactile stimuli, and i.t. nociceptin evoked hyperalgesia in response to noxious thermal stimuli in conscious mice. Here we have characterized the nociceptin-induced allodynia and compared it with the morphine-induced allodynia and the nociceptin-evoked hyperalgesia. 2 Nociceptin-induced allodynia was evoked by the ®rst stimulus 5 min after i.t. injection, reached a maximum at 10 min, and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 40 publications
(53 reference statements)
3
64
0
1
Order By: Relevance
“…We previously showed that intrathecal (i.t.) administration of Noc/OFQ at very low doses (picogram range) induced allodynia, a state of discomfort and pain evoked by innocuous tactile stimuli, as well as hyperalgesia in conscious mice (Okuda-Ashitaka et al, 1996;Hara et al, 1997). On the other hand, i.t.…”
mentioning
confidence: 99%
“…We previously showed that intrathecal (i.t.) administration of Noc/OFQ at very low doses (picogram range) induced allodynia, a state of discomfort and pain evoked by innocuous tactile stimuli, as well as hyperalgesia in conscious mice (Okuda-Ashitaka et al, 1996;Hara et al, 1997). On the other hand, i.t.…”
mentioning
confidence: 99%
“…morphine (Mogil et al, 1996). At the spinal level, intrathecal injection of low concentrations of nociceptin in mice causes allodynia and hyperalgesia (Hara et al, 1997), whereas at higher concentrations this peptide can cause analgesia (King et al, 1997;Tian et al, 1997). These effects are mediated at both a presynaptic site of action in afferent nerve terminals, and at a postsynaptic site of action on spinal interneurons (Neal et al, 1999).…”
mentioning
confidence: 99%
“…Hara et al showed that i.t. injection of nociceptin at 2.5 ng /kg induced the maximal allodynia in mice (27) and this dose corresponded to 50 pg /mouse (i.t.) which was used in this study.…”
Section: Discussionmentioning
confidence: 99%